Response Characteristics Analysis and Fatigue Life Assessment of Asphalt Pavement around the Manhole - Hong Zhang; Quanman Zhao; Can Peng (Shock and Vibration)
In view of the damage of the pavement around manholes, this paper proposes an effective way to analyse the stress characteristics of the road under vehicle load and evaluate the fatigue life of the pavement around manholes. A half vehicle-road-manhole cover coupling dynamic model is established to calculate the dynamic load coefficient. According to the finite element analysis (FEA) model in ABQUS, the dynamic response characteristics of the pavement around the manhole are analysed, and the stresses under different braking force and different vehicle type are compared. In addition, the fatigue life of the pavement surface layer under different loading conditions is calculated, and three different fatigue life models are selected to analyse the influence of different factors on the fatigue life of the pavement base structure around the manhole. The results show that the fatigue life of the pavement base layer decreases with the increase of manhole subsidence value, and the fatigue life increases with the increase in thickness of the surface layer, and the change of elastic modulus of the subgrade has no obvious influence on the fatigue life of road base. Finally, a fatigue life evaluation index based on high root energy is proposed to compare the three models more intuitively. Consequently, the analysis results can provide a basis for manhole surrounding pavement design and maintenance, and the analysis method is worthy of further application in the research of pavement fatigue life under more influencing factors.